Association of socioeconomic and practical unmet needs with self-reported nonadherence to cancer treatment appointments in low-income Latino and Black cancer patients. Issue 2 (3rd March 2016) - Costas-Muniz, Rosario; Leng, Jennifer; Aragones, Abraham; Ramirez, Julia; Roberts, Nicole; Mujawar, Mohammed Imran; Gany, Francesca
Abstract : Objective. Treatment adherence, with minimal numbers of missed appointments, is an important determinant of survival among cancer patients. This study aims to determine if unmet financial, logistic, and supportive care needs predict self-reported adherence to cancer treatment appointments of chemotherapy and/or radiation among low-income ethnic minority patients. Design. The sample included 1098 underserved Latino and Black patients recruited from cancer clinics in New York City through the Cancer Portal Project. Participants completed a survey which included sociodemographic, health-related questions and a needs assessment, in their preferred language. Patients' adherence to chemotherapy and/or radiation treatment appointments was assessed using a self-report. Results. A sample of 1098 patients (581 Latino and 517 Black cancer patients) was recruited. Forty-two Latino cancer patients (7.4%) and 78 Black cancer patients (15.5%) reported missing treatment appointments. Patients, who experienced four or more unmet needs (odds ratios [OR] = 2.02–3.36), and those with unmet housing needs (OR = 3.10–3.31), were more likely to report missing cancer treatment appointments, regardless of their ethnicity/race. Black patients with unmet supportive care (OR = 2.27) and health insurance needs (OR = 3.80) were more likely to miss appointments. Amongst Latinos, legal health-related issues (OR = 2.51) was a significant predictor of missed appointments. Conclusions. Among ethnic minority cancer patients, unmet socioeconomic and supportive care needs, housing needs in particular, predicted patient-reported missed radiation, and/or chemotherapy appointments. Future research should focus on exploring the impact of practical and supportive unmet needs on adherence and development of interventions aiming to improve cancer treatment adherence.